Middle School Teacher Self-Efficacy in the Implementation of the Learning Process in Indonesia - Yumnah, Siti; Judijanto, Loso; Pongpalilu, Fien; Syathroh, Isry Laila; Wibowo, Guntur Arie (Journal for Lesson and Learning Studies, 2024)
In the school environment, all teachers have a good level of teacher efficacy. However, in reality, many teachers still find low levels of efficacy. This has an impact on students' knowledge, understanding, and achievement in the school environment. This is urgent to be researched because there are similarities between theory, hope, and reality. So the research aims to analyze the factors that influence teachers' self-effectiveness in implementing Environmental Education in schools. The method in this research is quantitative research with regression. The subjects consisted of 300 teachers from private secondary schools and state secondary schools spread across Indonesia. Data collection techniques using instruments. Instruments developed from indicators and measured based on a Likert scale. Data analysis techniques using Statistics version 25.0 with descriptive (mean, standard deviation, frequency, and percentage) and inferential statistics using the Multiple Linear Regression method. The results and research findings show that the level of teacher self-efficacy in implementing Environmental Education in schools is moderate. It was found that the factors that influence teacher self-efficacy in the implementation of education are teacher awareness of the environment and teacher perceptions of the principal's learning leadership.